Region Based Cryptography: A Study of Difference Between the .jpg Image and .png Image After Recombined RGB Images - Bhat, Irfan Jalal; Mehra, Raghav; Chaturvedi, Amit Kumar (International Journal of Computer Sciences and Engineering, 2019)
Today is the age of information and technology. We cannot proceed even a single step without it. We are fully dependent on information and technology. In this paper we will show that which image is best after recombined of RGB image. First we take .jpg image, differentiate it and then recombined to obtained the final image and again we take the .png image, differentiate it RGB , recombined it to get final image .At last we will compare the final image of .jpg and .png and see different.